STANDARISASI DAN MANAJEMEN PENGELOLAAN KOTAK P3K DI SEKOLAH MELALUI PROGRAM SIAGA UKS - Risa Supriningrum; Oktavia Ramadhani Oktavia Ramadhani; Naailah Zalfa Naailah Zalfa (Jurnal Abdi Masyarakat Kita, 2026)
The SIAGA UKS community service programme aims to improve the quality of school health facility management through education on standardising the contents of first-aid kits, a medicines management system to prevent expiry, and the enhancement of practical skills among UKS staff. The activity took place in May 2026 at SMAN 8 Samarinda with 32 Year 10 pupils participating. The methods used included interactive lectures using PowerPoint presentations, hands-on demonstrations of the use of portable diagnostic test kits, and assessment via pre-tests and post-tests. The results of the activity showed a significant improvement in the students’ understanding, with all participants (100 per cent) able to answer the post-test questions correctly, particularly regarding the indicator for restricted-use medicines. The independent demonstration sessions successfully boosted the students’ confidence in using medical equipment hygienically. A continuous education programme is recommended to maintain first-aid readiness in schools.